KOMPARASI PENERAPAN MODEL PEMBELAJARAN INKUIRI DAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA SISWA KELAS X SMKN 1 SUMATERA BARAT - M. Ridho Fadillah; Delsina Faiza; Thamrin Thamrin (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
This research was focus on the low of student’s learning outcome, specially on Basic Electricity and Electronics subject at SMKN 1 Sumatera Barat. The objective is to reveal the comparisons of applying inquiry learning model and problem based learning model to the subject. By using Quasi experimental with simple random sampling; one of probability sampling tecnique, the Inqury model was enducted in experiment class and The Other class where PBL learning model, was also implemented to compare the treatment. The primary data was collected by structured  test (Pre-test and Post-test) according to basic competences described of the subject. based on the t-test result, complying the pre-requisite test such as normalityexamination, this research found that t0≥t ≥ t0 (-2,052 ≥ 2,55  ≥  2,052). However, the result has shown that inquiry learning model is providing better student’s learning outcome than PBL model. Therefore, the inquiry model is more effective than PBL model as research conclusion.Keywords: learning outcomes, learning model, Inquiry, Problem Based Learning.